Edukasi dan Implementasi Manajemen Keuangan dalam Upaya Peningkatan Kapasitas UMKM di Kelurahan Benda Baru, Kota Tangerang Selatan - Ani Suryani; Melly Andini; Rina Sulistiawati; Ismail Nur Hidayat; Nofryanti N; Baharudin Saga (Yayasan Daarul Huda Kruengmane, 2025)
The low level of financial management literacy among micro, small, and medium enterprises (MSMEs) remains a key barrier to effective and sustainable business operations. This community service program aims to enhance the understanding and skills of MSME actors in basic financial recording, cash flow management, SWOT analysis, and financial decision-making. The methods applied include socialization, technical training, practical simulations, technical assistance, and evaluation through pre-tests and post-tests. The results indicate a significant improvement in participants’ abilities to record daily transactions, prepare cash flow statements, calculate cost of goods sold, and assess their business position using SWOT analysis. Beyond knowledge enhancement, the program also generated positive behavioral changes and fostered the emergence of local leaders who initiated collaborative bookkeeping practices within the MSME community. This program proved effective in strengthening MSME financial capacity and promoting more accountable and sustainable business governance.